Prolonged QT predicts prognosis in COVID‐19. Issue 5 (13th April 2021) - Akhtar, Zaki; Gallagher, Mark M.; Yap, Yee Guan; Leung, Lisa W. M.; Elbatran, Ahmed I.; Madden, Brendan; Ewasiuk, Victoria; Gregory, Louise; Breathnach, Aodhan; Chen, Zhong; Fluck, David S.; Sharma, Sumeet
Abstract: Background: Coronavirus disease‐2019 (COVID‐19) causes severe illness and multi‐organ dysfunction. An abnormal electrocardiogram is associated with poor outcome, and QT prolongation during the illness has been linked to pharmacological effects. This study sought to investigate the effects of the COVID‐19 illness on the corrected QT interval (QTc). Method: For 293 consecutive patients admitted to our hospital via the emergency department for COVID‐19 between 01/03/20 ‐18/05/20, demographic data, laboratory findings, admission electrocardiograph and clinical observations were compared in those who survived and those who died within 6 weeks. Hospital records were reviewed for prior electrocardiograms for comparison with those recorded on presentation with COVID‐19. Results: Patients who died were older than survivors (82 vs 69.8 years, p  < 0.001), more likely to have cancer (22.3% vs 13.1%, p  = 0.034), dementia (25.6% vs 10.7%, p  = 0.034) and ischemic heart disease (27.8% vs 10.7%, p  < 0.001). Deceased patients exhibited higher levels of C‐reactive protein (244.6 mg/L vs 146.5 mg/L, p  < 0.01), troponin (1982.4 ng/L vs 413.4 ng/L, p  = 0.017), with a significantly longer QTc interval (461.1 ms vs 449.3 ms, p  = 0.007). Pre‐COVID electrocardiograms were located for 172 patients; the QTc recorded on presentation with COVID‐19 was longer than the prior measurement in both groups, but was more prolonged in the deceased group (448.4 ms vs 472.9 ms, pre‐COVID vs COVID, p  < 0.01). Multivariate Cox‐regression analysis revealed age, C‐reactive protein and prolonged QTc of >455 ms (males) and >465 ms (females) ( p  = 0.028, HR 1.49 [1.04‐2.13]), as predictors of mortality. QTc prolongation beyond these dichotomy limits was associated with increased mortality risk ( p  = 0.0027, HR 1.78 [1.2‐2.6]). Conclusion: QTc prolongation occurs in COVID‐19 illness and is associated with poor outcome.